Nurse practitioner caseload in primary health care: Scoping review. (October 2016) - Martin-Misener, Ruth; Kilpatrick, Kelley; Donald, Faith; Bryant-Lukosius, Denise; Rayner, Jennifer; Valaitis, Ruta; Carter, Nancy; Miller, Patricia A.; Landry, Véronique; Harbman, Patricia; Charbonneau-Smith, Renee; McKinlay, R. James; et al.
Abstract: Objectives: To identify recommendations for determining patient panel/caseload size for nurse practitioners in community-based primary health care settings. Design: Scoping review of the international published and grey literature. Data sources: The search included electronic databases, international professional and governmental websites, contact with experts, and hand searches of reference lists. Eligible papers had to (a) address caseload or patient panels for nurse practitioners in community-based primary health care settings serving an all-ages population; and (b) be published in English or French between January 2000 and July 2014. Level one testing included title and abstract screening by two team members. Relevant papers were retained for full text review in level two testing, and reviewed by two team members. A third reviewer acted as a tiebreaker. Data were extracted using a structured extraction form by one team member and verified by a second member. Descriptive statistics were estimated. Content analysis was used for qualitative data. Results: We identified 111 peer-reviewed articles and grey literature documents. Most of the papers were published in Canada and the United States after 2010. Current methods to determine panel/caseload size use large administrative databases, provider work hours and the average number of patient visits. Most of the papers addressing the topic of patient panel/caseload size in community-based primary health care were descriptive. The average number of patients seen by nurse practitioners per day varied considerably within and between countries; an average of 9–15 patients per day was common. Patient characteristics (e.g., age, gender) and health conditions (e.g., multiple chronic conditions) appear to influence patient panel/caseload size. Very few studies used validated tools to classify patient acuity levels or disease burden scores. Discussion: The measurement of productivity and the determination of panel/caseload size is complex. Current metrics may not capture activities relevant to community-based primary health care nurse practitioners. Tools to measure all the components of these role are needed when determining panel/caseload size. Outcomes research is absent in the determination of panel/caseload size. Conclusion: There are few systems in place to track and measure community-based primary health care nurse practitioner activities. The development of such mechanisms is an important next step to assess community-based primary health care nurse practitioner productivity and determine patient panel/caseload size. Decisions about panel/caseload size must take into account the effects of nurse practitioner activities on outcomes of care.